Selective serotonin reuptake inhibitors and the risk of bleeding - L, Padma; Ramanujam, Ranjani; Thimmaiah, Rohini S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Selective serotonin reuptake inhibitors (SSRIs) are commonly prescribed agents for various conditions in general psychiatry. There is a strong consensus that blockade of serotonin reuptake affects primary hemostasis, namely platelet activity, thus resulting in a bleeding tendency. Considering that SSRIs are commonly prescribed, this study was conducted to assess if they were associated with an increased risk of bleeding. Methods: This was a prospective, open-label study of 30 patients attending the Psychiatry out-patient department, Dr. B. R. Ambedkar Medical College, Bangalore who satisfied DSM-IV criteria for a primary diagnosis of depression, treated with SSRIs. Bleeding time, clotting time, prothrombin time, partial thromboplastin time and platelet count were assessed at baseline and at the end of 6 weeks of treatment or occurrence of bleeding symptom. Results: The patients aged between 18-55 years of whom 21 were females, were treated with an SSRI (fluoxetine 12, escitalopram 12 and sertraline 6 patients). Six patients had overt symptoms of bleeding (upper gastrointestinal bleeding (hematemesis) 4; epistaxis 2 and petechiae 2) of whom one patient gave a history of both hematemesis and petechiae and another of hematemesis and epistaxis. The average day after treatment beginning, on which patients reported with bleeding was 30.33 (26-40 days). There was a significant increase in the bleeding time (p=0.028) and clotting time (p=0.042), implying derangement in platelet aggregation. There was no significant change in the other parameters. Conclusion: Treatment with SSRIs increases the risk of bleeding. However, large, randomized controlled trials are required to re-affirm these findings.